Fresh fruit bunch production of oil palm plantation in the lowland area of Sembilang Dangku Landscape. (October 2019) - Segara, Rio Octarizza; Hariyadi,; Sukarman,; Santoso, Kresno Dwi
Abstract: The results of the study showed that Sembilang Dangku Landscape had known two types of soil namely peat soil and mineral soil. Detail information for peat soil in this area namely Typic Haplosaprists and Typic Haplohemists meanwhile, for mineral soil, there are two types of soil that have been identified at these locations namely Inceptisols (Typic Endoaquepts and Typic Humaquepts) and Entisols (Typic Sulfaquents). This study aimed to analyze the production of oil palm plantations in lowland areas on marginal land. This research was conducted at six locations of oil palm plantations in Musi Banyuasin Regency, South Sumatra province. The methods used were descriptive quantitative and qualitative calculation of FFB (fresh fruit bunches) production that compared the standard potential production of the Palm Oil Research Center (PPKS referred in Indonesia ). The yield of FFB oil palm productivity (ton/ha) on marginal land showed that Typic Haplosaprists, Typic Haplohemists and Typic Endoaquepts, Typic Humaquepts did not have a significant effect because yield from plantation management produced FFB production oil palm was quite good. The effect that has quite a different production is Entisols (Typic Sulfaquents) or L6 locations. Based on this research, the type of soil is a factor that greatly affects the productivity of oil palm.